The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1530/acta.0.1280215
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of mitogenesis in human thyroid epithelial cells by endothelin

Abstract: We investigated whether a potent vasoconstrictor, endothelin, stimulated the proliferation of human thyroid epithelial cells (thyrocytes).[3H]-thymidine incorporation into normal thyrocytes and thyrocytes from patients with Graves' disease was significantly increased at 10-9 mol/l endothelin. reaching a plateau at 10-8 mol/l. The proliferative responses of the thyrocytes obtained from patients with Graves' disease were similar to those of normal thyrocytes. Furthermore, the cell number of thyrocytes stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Significantly elevated ET-1 plasma levels in patients with Graves disease are consistent with reports of other authors (Eguchi et al, 1993;Letizia et al, 1995), who demonstrate that thyrocytes from healthy controls and from patients with Graves disease can be stimulated to pro- liferate by ET-1, whereby the mitogenic response to ET-1 was greater for Graves disease thyrocytes (Eguchi et al, 1993). Letizia et al investigated 25 hyperthyroid patients, 16 patients with Graves disease, and an age-matched healthy control group of 21 individuals (Letizia et al, 1995).…”
Section: Discussionsupporting
confidence: 80%
“…Significantly elevated ET-1 plasma levels in patients with Graves disease are consistent with reports of other authors (Eguchi et al, 1993;Letizia et al, 1995), who demonstrate that thyrocytes from healthy controls and from patients with Graves disease can be stimulated to pro- liferate by ET-1, whereby the mitogenic response to ET-1 was greater for Graves disease thyrocytes (Eguchi et al, 1993). Letizia et al investigated 25 hyperthyroid patients, 16 patients with Graves disease, and an age-matched healthy control group of 21 individuals (Letizia et al, 1995).…”
Section: Discussionsupporting
confidence: 80%
“…The participation of ETs in mitogenesis involves activation of multiple transduction pathways, such as the production of second messengers, the release of intracellular pools of calcium and synergism with various growthfactors (Battistini et al, 1993;Kennedy et al, 1993;Masaki, 1993) which are well known to participate in the pathogenesis of thyroid growth. In humans, the relationship between the thyroid gland and ETs was established by some researchers who demonstrated the presence of specific high-affinity receptors for ET1 in thyroid cells (Tsushima et al, 1994) and showed that ET1 is able to stimulate proliferation of thyroid epithelial cells in both normals and patients with Graves' disease (Eguchi et al, 1993). Our data show that the presence of cystic thyroid nodules is associated with a significant increase in cystic and plasma i-ET levels.…”
Section: Discussionsupporting
confidence: 69%
“…Recent data have shown the presence of immunoreactive ET1 in rat and porcine thyroid follicular cells (Colin et al, 1992), in which this peptide is able to negatively regulate TSH-induced iodide uptake (Tsushima et al, 1994). Moreover, specific highaffinity receptors for ET have been identified on human thyrocytes, and it has been shown that ETs are able to stimulate the proliferation of thyrocytes from normal thyroid tissues and tissues from patients with Graves' disease (Eguchi et al, 1993). Literature data on i-ET levels in patients with thyroid diseases are scanty.…”
mentioning
confidence: 99%
“…ET-1 is mainly produced by the endothelial cells of the vasculature. 99 In the rat goiter model, ET-1 mRNA and protein levels increased 3.5-and 5-fold, respectively, during hyperplasia. ETA is located on smooth muscle cells, where activation of this receptor causes vasoconstriction.…”
Section: Endothelin-1 and Atrial Natriuretic Peptidementioning
confidence: 92%